Pemenuhan Hak Pekerja yang Terkena PHK dalam Pandangan Hubungan Industrial (Beberapa Studi Kasus Perusahaan di Indonesia) - Aldi Bagas Herlambang; Muhamad Rizal; Sari Usih Natari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Writing this article aims to find out how to fulfill the rights that will be obtained by workers when these workers experience layoffs. The method used is a qualitative method using literature studies related to the law on fulfilling the rights of layoff workers. Fulfillment of these rights will be based on the applicable laws and regulations. Fulfillment of the rights obtained by workers affected by layoffs has been regulated through Law No. 13 of 2003 concerning Manpo wer and is also regulated in Law No. 6 in 2023 with a few changes. In reality, the application of these regulations has been carried out well. Although there are still several companies that do not fulfill workers' rights as regulated in legislation. This article also explains what workers get or what rights they get in accordance with the policies in force in granting workers’ rights. Policies or regulations that exist in Indonesia are a form of legal protection in industrial relations for both workers and employers in guaranteeing the rights they obtain.